Analisisi Energi Listrik Terselamatkan pada Penyulang Bangli PT. PLN (Persero) Area Bali Timur dengan Beroperasinya PLTS Kayubihi - gambut, valentinus gerald; Hartati, Rukmi Sari; Weking, Antonius Ibi (Majalah Ilmiah Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2016.v15i01p12, 2016)
Abstract— Bangli Feeder has 3 Feeder, namely Kota Feeder, Kayubihi Feeder and Tembuku Feeder. This Feeder has a main power supply is obtained from the Gianyar Main Relay Station. Currently Kayubihi Solar Cell Power Plant directly interconnected to the Feeder Bangli. With Solar cell power plant connected on Kayubihi Feeder, it will result in a change in the performance of feeder Bangli. This involves changes in the performance of of the electrical energy that is channeled along the Bangli feeder system reliability. The addition of the feeder solar cell power plant create electrical energy saved Bangli feeder decline. Bangli feeder without generating large solar power energy not supplied amounted to 10.426 kWh. Energy not supplied Bangli Feeder after obtaining additional supplies of solar power generating is 1.505 kWh.
Keywords: PLTS, ENS (Energy Not Supplied),AENS (Average Energy Not Supplied).